Perancangan Sistem Informasi Masyarakat Berbasis Web Mobile di Komplek Perumahan Puri Cendekia I Jatinangor - Firman Hamdani (Masoem University, 2020)
In recording population data at Puri Cendekia 1 Jatinangor Housing conducted by the Head of RT, it is still done conventionally. This raises several problems, namely: difficulties in knowing occupant / resident data information that can only be known by the head of the RT, so that many residents of the complex do not know their neighbors, recording and information services of the community in a complex environment is still limited by space and time, so that if there is a need from the community can only be done at certain hours, conventional records in the population book are at risk of damage and loss of data. In this research the system development method used is using the OOAD (Object Oriented Analysis and Design) method with the RUP (Rational Unified Process) model, which consists of several stages, namely: Business Modeling, Requirements, Analysis and Design, Implementation, Test, Deployment. As for the system development tools using UML (Unified Modeling Language) which consists of: Use Case Diagrams, Activity Diagrams and Class Diagrams. With the design of a Mobile Web-based community information system, it is expected to be able to: Make it easier in finding data on residents of housing complexes, Simplify data collection and community services without being limited by space and time, Avoiding damage and loss of data.